Children, Paternalism and the Development of Autonomy - Mullin, Amy (Ethical theory and moral practice, 2014)
This paper addresses the issue of paternalism in child-rearing. Since the parent–child relationship seems to be the linguistic source of the concept, one may be tempted to assume that raising a child represents a particularly appropriate sphere for paternalism. The parent–child relationship is generally understood as a relationship that is supposed to promote the development and autonomy-formation of the child, so that the apparent source of the concept is a form of autonomy-oriented paternalism. Far from taking paternalism to be overtly unproblematic in such paradigmatic, pedagogical settings, this article analyzes how an effort should be made to understand a child’s capacities and which standards parents should be held to when deciding whether interference truly serves the child’s interests.